2017
DOI: 10.3126/njdvl.v15i1.18054
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole – Induce Black Hairy Tongue- A Case Report

Abstract: Lansoprazole induced black hairy tongue has been rarely reported. The purpose of this paper is to report a case of lansoprazole induce black hairy tongue and review the literature. A 75 year man from eastern part of Kathmandu presented with black hairy fine growth from tongue along with discomfort, burning and halitosis from oral cavity after taking lansoprazole for acute peptic disease(APD) from over the counter and after discontinuation of lansoprazole, black hairy tongue was resolving. Clinically and histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Aryal et al reported a case of Lansoprazole induced BHT in 2017. 6 PPI induced BHT is possibly due to alteration of the pH of gastric acid in the stomach and a decrease in saliva production which may lead to defective desquamation of the dorsal surface of the tongue thereby accumulating a keratinized layer and allowing the growth of candida species and porphyrin producing chromogenic organisms in the oral flora giving the characteristic colour. Accumulation of keratinized layer causes hypertrophy and elongation of filiform papillae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aryal et al reported a case of Lansoprazole induced BHT in 2017. 6 PPI induced BHT is possibly due to alteration of the pH of gastric acid in the stomach and a decrease in saliva production which may lead to defective desquamation of the dorsal surface of the tongue thereby accumulating a keratinized layer and allowing the growth of candida species and porphyrin producing chromogenic organisms in the oral flora giving the characteristic colour. Accumulation of keratinized layer causes hypertrophy and elongation of filiform papillae.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking, consumption of heavy black tea or coffee, poor oral hygiene associated with HIV, malignancy, trigeminal neuralgia, and medications like antipsychotics, methyldopa, antidepressants, anticancer medicines and antibiotics have been reported to cause BHT. 6,7 The purpose of this article is to present a case of pantoprazole induced BHT, which has been rarely reported till date.…”
Section: Introductionmentioning
confidence: 99%
“…BHT is associated with predisposing factors like bad oral hygiene, excessive black tea / coffee consumption, general debilitation, xerostomia, male gender, older age, prolonged use of oxidizing mouthwashes, advanced cancer, HIV and graftversus-host disease 1 . Medications include antibiotics, corticosteroids, oxygenating mouth rinses, glycopyrrolate, lorazepam and psychotropic drugs 2,5,6 . Antibiotics may alter oral microbial flora leading to trapping of foreign material and overgrowth of chromogenic microorganisms 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics may alter oral microbial flora leading to trapping of foreign material and overgrowth of chromogenic microorganisms 2 . The protective function of saliva is lost in xerostomia, predisposing to BHT 2,5 . It is difficult to point out which antibiotic was the cause of BHT as he has had two antibiotics.…”
Section: Discussionmentioning
confidence: 99%